(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In the history of world linguistics, different and various approaches to the language phenomenon have appeared. Language is a means of social communication with a specific structure, and its basis is a lexical unit. This article provides information about the lexical units of business and economy, which were formed in foreign languages and entered the Uzbek language, what are the lexical combinations, their characteristics and categories. The article also discusses the formation of neologisms imported from foreign languages. The meaning of each lexical unit is analyzed in the article.